Orally delivered Bacillus subtilis expressing chicken NK-2 peptide stabilizes gut microbiota and enhances intestinal health and local immunity in coccidiosis-infected broiler chickens - Samiru S. Wickramasuriya; Inkyung Park; Youngsub Lee; Luciana M. Richer; Chris Przybyszewski; Cyril G. Gay; Jolieke G. van Oosterwijk; Hyun S. Lillehoj (Poultry Science, 2023)
ABSTRACT: We recently reported a stable Bacillus subtilis-carrying chicken NK-lysin peptide (B. subtilis-cNK-2) as an effective oral delivery system of an antimicrobial peptide to the gut with therapeutic effect against Eimeria parasites in broiler chickens. To further investigate the effects of a higher dose of an oral B. subtilis-cNK-2 treatment on coccidiosis, intestinal health, and gut microbiota composition, 100 (14-day-old) broiler chickens were allocated into 4 treatment groups in a randomized design: 1) uninfected control (CON), 2) infected control without B. subtilis (NC), 3) B. subtilis with empty vector (EV), and 4) B. subtilis with cNK-2 (NK). All chickens, except the CON group, were infected with 5,000 sporulated Eimeria acervulina (E. acervulina) oocysts on d 15. Chickens given B. subtilis (EV and NK) were orally gavaged (1 × 1012 cfu/mL) daily from d 14 to 18. Growth performances were measured on d 6, 9, and 13 postinfection (dpi). Spleen and duodenal samples were collected on 6 dpi to assess the gut microbiota, and gene expressions of gut integrity and local inflammation makers. Fecal samples were collected from 6 to 9 dpi to enumerate oocyst shedding. Blood samples were collected on 13 dpi to measure the serum 3–1E antibody levels. Chickens in the NK group showed significantly improved (P < 0.05) growth performance, gut integrity, reduced fecal oocyst shedding and mucosal immunity compared to NC. Interestingly, there was a distinct shift in the gut microbiota profile in the NK group compared to that of NC and EV chickens. Upon challenge with E. acervulina, the percentage of Firmicutes was reduced and that of Cyanobacteria increased. In NK chickens, however, the ratio between Firmicutes and Cyanobacteria was not affected and was similar to that of CON chickens. Taken together, NK treatment restored dysbiosis incurred by E. acervulina infection and showed the general protective effects of orally delivered B. subtilis-cNK-2 on coccidiosis infection. This includes reduction of fecal oocyst shedding, enhancement of local protective immunity, and maintenance of gut microbiota homeostasis in broiler chickens.